If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -1x + -6 = 0 Reorder the terms: -6 + -1x + 3y = 0 Solving -6 + -1x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + -1x + 6 + 3y = 0 + 6 Reorder the terms: -6 + 6 + -1x + 3y = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1x + 3y = 0 + 6 -1x + 3y = 0 + 6 Combine like terms: 0 + 6 = 6 -1x + 3y = 6 Add '-3y' to each side of the equation. -1x + 3y + -3y = 6 + -3y Combine like terms: 3y + -3y = 0 -1x + 0 = 6 + -3y -1x = 6 + -3y Divide each side by '-1'. x = -6 + 3y Simplifying x = -6 + 3y
| -3k+1=-6-4k | | 4x+48=90 | | 8u^2-14u+3= | | x-1-7=16 | | -1/3/2/15 | | -2y+15=10 | | Z-6=-36 | | 4/4x=48/4 | | 5x^3+8y^2-30x+16y+13=0 | | 12(3x^2-59x-72)=0 | | (31/10)s=(31/5) | | T-16=-23 | | 4+5t-3=8t+3-2t | | 4/4=48/4 | | 4a-5a= | | 0.5(m-2)=5 | | x/9=29=41 | | n/7=-42 | | -b/6-7=-11 | | 8x^2-70x+17= | | 3(1/10)s=6(1/5) | | 14/3-2 | | cos3.14/4 | | g(n)=n^2+4 | | 3a+-2a=-17 | | 1=-4/3(-4) | | 10=-5/6× | | 12x+36=7x | | 1-3(-1+2v)-3v= | | cx-d=0solvex | | 8/t;t=4 | | 12(2x^2-11x-40)=0 |